# |
ODE |
Mathematica |
Maple |
\[
{}\left (x^{2}+x \right ) y^{\prime \prime }+\left (-x^{2}+2\right ) y^{\prime }-\left (x +2\right ) y = x \left (1+x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y^{\prime \prime }+x y^{\prime }-y = \left (1-x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = x^{2} {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = x \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+3 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\frac {x y^{\prime }}{x -1}+\frac {y}{x -1} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x \left (x +2\right ) y^{\prime }+\left (x +2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x f \left (x \right ) y^{\prime }+f \left (x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+2 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }+3 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+6 y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+5 y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 a^{2} y^{\prime \prime }+a^{4} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 a^{2} y^{\prime \prime }+a^{4} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+2 y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-2 y^{\prime \prime }-6 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }-3 y^{\prime \prime }-5 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}-6 y^{\prime \prime \prime \prime }-8 y^{\prime \prime \prime }+48 y^{\prime \prime }+16 y^{\prime }-96 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime } = \sin \left (x \right )+24
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+2 y^{\prime } = 10+42 \,{\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+3 x^{2} y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime \prime }+8 x^{2} y^{\prime \prime \prime }+8 x y^{\prime \prime }-8 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-5 y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = {\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }+4 y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+4 y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime } = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = 2 x -1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-y = x \,{\mathrm e}^{x} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \sec \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = x \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime }+y = \frac {2}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \tan \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 3 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = -8 \sin \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = x^{2}+2 x +2
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = \frac {x -1}{x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = -3 \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -3 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\sin \left (y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = x^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y
\] |
✓ |
✗ |
|
\[
{}x^{2} y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{x} = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{x} = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{\sqrt {-x^{2}+1}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x -y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x -y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 x y^{\prime }-y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-x^{2} y = 1
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\left (1+x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|